2023
DOI: 10.1080/14786419.2023.2200945
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of semiochemicals from three stored product beetles by headspace solid-phase microextraction coupled with gas chromatography–mass spectrometry

Abstract: Solid-phase microextraction (SPME) fibre (50/30 µm Divinylbenzene / Carboxen / Polydimethylsiloxane) was purchased from Supleco, USA. Alkane standard solution (C8-C20; ⁓40 mg/L each in hexane) was procured from Sigma-Aldrich (Switzerland) for the determination of the Kováts retention index (KRI) of compounds. The nonanal (NL), lauric acid (LA) and stearic acid (SA) analytical standards were purchased from Sigma-Aldrich (USA) to confirm compounds secreted from beetles. Insect cultureStored product insect pests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Tian XM concluded that 1-pentadecene could be a potential volatile biomarker for the presence of T. castaneum during the transport of brown rice [ 21 ]. Madhurya Lokesh detected 2-ethyl-p-benzoquinone in T. castaneum but not in Callosobruchus maculatus (Pulse beetle) and Sitophilus oryzae (Rice weevil) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tian XM concluded that 1-pentadecene could be a potential volatile biomarker for the presence of T. castaneum during the transport of brown rice [ 21 ]. Madhurya Lokesh detected 2-ethyl-p-benzoquinone in T. castaneum but not in Callosobruchus maculatus (Pulse beetle) and Sitophilus oryzae (Rice weevil) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%